Patrimônio bibliográfico de C&T em universidades: proposta para formação das coleções especiais da Biblioteca Paulo Geyer - Souza, Ingrid Lopes de (2017)
This study is focused on bibliographic heritage of Science and Technology in universities. Its main objective is to propose criteria that can be applied to university libraries in the formation of their special collections, based on the Paulo Geyer Library experience. Characterizes the Paulo Geyer Library as a guardian of university bibliographic heritage of S & T in the context of the School of Chemistry. Analyzes libraries as memory places. It also tackles the importance of university libraries as guardians of bibliographic heritage of Science and Technology, and the relevance of developing special collections. It proposes to highlight the significance of Paulo Geyer Library as well as the conception of heritage, analyzing it according to national and international legislation. Ranking the works which could be part of the special collection using tables. It defines some criteria for selecting the works. As a methodology it carries out the bibliographic research with characteristics of applied research given its practical interest.